A preliminary survey of freshwater snails from selected barangays in the elevated region of Palo, Leyte. - Garcia, Katrina A. (Katrina A. Garcia, 2018)
The municipality of Palo has no updated inventory regarding the biodistribution of freshwater gastropod species found in the locality. Thus, this study is aimed to survey the freshwater snails present in the municipality, particularly in the elevated terrains. Freshwater snails were collected in selected barangays through intensive sampling and ring sampling in March to April 2018.